2015
DOI: 10.7860/jcdr/2015/13132.6068
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Dengue Fever-Cerebral Venous Thrombosis

Abstract: A 16-year-old boy presented to our tertiary care centre in puducherry in the month of October 2014 with high grade, intermittent fever for 10 days duration. He had double vision involving left eye and headache for two days duration. He had multiple erythematous lesion all over the body on 3 rd day of fever. At home his skin rash was assumed as chicken pox by mother; he was kept at home and treated conservatively with antipyretics.As he developed double vision he was referred to our hospital. There was no vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Ku et al 2 reported a case of Pulmonary embolism in a patient with dengue and influenza A coinfection from Taiwan. Cases of cerebral venous thrombosis after DF were reported by Tilara et al 9 and Vasanthi et al 10 …”
Section: Discussionmentioning
confidence: 91%
“…Ku et al 2 reported a case of Pulmonary embolism in a patient with dengue and influenza A coinfection from Taiwan. Cases of cerebral venous thrombosis after DF were reported by Tilara et al 9 and Vasanthi et al 10 …”
Section: Discussionmentioning
confidence: 91%
“…1 We were able to find two case reports of CVT in dengue in literature. 2,3 In both these reports, patients improved subsequently with adequate fluids and anticoagulation, with none of them requiring surgical intervention. Our patient had normal hematocrit values and she was being adequately hydrated.…”
Section: Discussionmentioning
confidence: 96%
“…Da Costa et al reported an incidence of 5.4% thrombotic events in patients with severe dengue with a total of 5 venous thrombotic events, 4 of the cases were DVT and 1 mesenteric venous thrombosis; nonetheless, it was not an isolated event since concomitantly Escherichia coli bacteremia, a well-known risk factor for portal vein thrombosis, was diagnosed [ 4 ]. Other thrombotic events associated with dengue described in the literature are mainly cerebral venous thrombosis and DVT; in many of these cases, an associated procoagulant factor was not found either [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of the disease can range from mild symptoms to more severe but infrequent manifestations such as septic shock and coagulation disorders [3], where hemorrhagic events predominate. Cases of thrombosis are exceptional and only a few have been reported in the literature [4][5][6].…”
Section: Introductionmentioning
confidence: 99%